THE INFLUENCE OF ENVIRONMENT ON JANE EYRE'S BEHAVIOR IN CHARLOTTE BRONTE'S JANE EYRE: A BEHAVIORIST PERSPECTIVE - SUYADI, EKO (2007)
In this study, the researcher attempts to explore the influences of the environment on the major character Jane Eyre in the Charlotte Bronte's Jane Eyre. The objective of the study is to analyze Jane Eyre in Charlotte Bronte's novel based on the structural element and to analyze the major character behavior based on the psychological approach, especially behaviorist perspective. In analyzing Jane Eyre the writer uses behaviorist approach and qualitative method. The object of the research is the behavior of the major character derived from Charlotte's novel published in 1967, by Pan Books LTD: London, 33, of Hill Street London, S.W.I. The data are literary data that consist of primary and secondary data. The primary data source is Jane Eyre's novel by Charlotte Bronte. The secondary data sources are the books about behaviorist and theories of personality and the other materials related to the analysis. The method of the data collection technique of this research is the library research. The result of the study shows the following conclusion. Firstly, there is a close relationship between literary works and psychological phenomenon. Secondly, the psychological analysis, specifically behaviorism falls into general curriculum that human's behavior is influenced by the personality and environment where they live. The dominant influence that builds Jane Eyre's personality is the characters in the environment where she stays.